Hepatic trace element concentrations of breeding female common eiders across a latitudinal gradient in the eastern Canadian Arctic. Issue 1 (15th November 2017) - Mallory, Conor D.; Gilchrist, H. Grant; Robertson, Gregory J.; Provencher, Jennifer F.; Braune, Birgit M.; Forbes, Mark R.; Mallory, Mark L.
Abstract: We examined hepatic concentrations of arsenic (As), cadmium (Cd), copper (Cu), lead (Pb), manganese (Mn), mercury (Hg), rubidium (Rb), selenium (Se) and zinc (Zn) in 10 breeding female common eiders ( Somateria mollissima ) from each of three colonies across 20° of latitude. Levels of many elements were elevated in eiders, although generally below levels of toxicological concern. We found significant differences in concentrations of As, Rb, Hg, Mn and Se among colonies, but not in a consistent pattern with latitude, and Hg:Se molar ratios did not vary among colonies. Furthermore, overlap in element concentrations from birds at different colonies meant that we could not reliably differentiate birds from different colonies based on a suite of their hepatic trace element concentrations. We encourage other researchers to assess baseline trace element levels on this important, harvested species, as a means of tracking contamination of nearshore benthic environments in the circumpolar Arctic. Highlights: Many elements were elevated in eiders, but generally below toxicological concern. We found significant differences in concentrations of some elements among colonies. We did not find a consistent pattern in concentrations with latitude.